Are congenital vertebral anomalies and spina bifida cystica aetiologically related?. Issue 6 (December 1981) - Lendon, R G; Wynne-Davies, R; Lendon, M
Abstract : Radiological records of 104 patients with multiple vertebral anomalies without apparent spina bifida and 112 infants with spina bifida cystica were surveyed and the incidences of hemivertebrae and of rib, vertebral body, and vertebral arch fusions were recorded. The distributions of these four anomalies along the vertebral axis were found not to be statistically different between the two age groups. This is additional evidence to support the hypothesis that multiple vertebral anomalies and anencephaly-spina bifida cystica are aetiologically related.